Strategi Pembelajaran Masa Pandemi (Studi Kasus di MA Al Hamid) - Dinar Saharani; Rais Hidayat (Journal on Education, 2024)
The purpose of this article is to describe learning strategies during the Covid-19 pandemic, at MA Al Hamid, East Jakarta. This qualitative research uses a case study type. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used is Miles and Huberman interactive analysis and data validity testing techniques using the triangulation method. The research results show that to ensure the continuity of the teaching and learning process during the pandemic, madrasas need to develop new learning strategies that are effective and efficient to achieve learning goals and objectives. The results of research on learning strategies during the pandemic include five management functions: (1) Planning, starting from socialization, training, technology adaptation, preparing madrasa policies related to the learning process, preparing online lesson plans; (2) Organizing, namely arranging the implementation of learning, by arranging online schedules and limited face-to-face methods (TTM); (3) Actuating, namely the process of implementing learning that has been designed, namely online, and limited face-to-face; (4) Controlling, a monitoring system from madrasah supervisors and parents, and (5) Evaluating, namely the online evaluation and assessment process using the El-Mantab application, Google Form and Whatsapp for accurate and objective documentation of learning results. The implications of the findings of this research should be input and consideration for the government in determining education policies during a pandemic or disaster